Agrarian Reform as Housing Justice: Transforming Land for Equitable Flat Access in Cirebon - Al-Mahrouqi, Aisha; Rinduni, Ridha; Williams, Noah (Universitas Negeri Semarang, 2025)
Land transformation through agrarian reform as an effort to ensure equitable access to adequate housing, particularly vertical housing (flats) in Cirebon. Agrarian reform is positioned not merely as land redistribution but also as a strategic instrument in providing housing for low-income communities. This approach aims to address land ownership inequality and enhance housing affordability through collaboration between the government and the public. The study demonstrates that agrarian reform can serve as an innovative solution to the housing crisis and social inequality in urban areas.